Superior microporous development in teak sawdust-derived activated carbon via N₂ activation for enhanced methylene blue uptake - I Gusti Agung Kade Suriadi; Dewa Ngakan Ketut Putra Negara; Tjokorda Gede Tirta Nindhia; I Gusti Agung Ketut Chatur Adhi Wirya Aryadi (JRTI (Jurnal Riset Tindakan Indonesia), 2026)
This study investigates the effect of activation atmosphere (N₂ and CO₂) on the physicochemical properties and adsorption performance of teak sawdust-derived activated carbon for methylene blue removal. Carbonization was conducted at 750 °C followed by physical activation at 700 °C with a gas flow rate of 200 mL min⁻¹. Characterization results showed that N₂ activation produced a higher specific surface area and micropore volume compared to CO₂ activation, indicating more dominant microporous development. The N₂-activated sample exhibited superior adsorption uptake toward methylene blue under the tested condition (5 ppm), reaching 13.30 mg g⁻¹, while the CO₂-activated carbon showed lower uptake. The findings suggest that activation atmosphere strongly influences pore evolution and adsorption behavior. However, adsorption performance was evaluated at a single concentration; therefore, further isotherm and kinetic studies are required to determine the true maximum adsorption capacity and adsorption mechanism.